Three New Species of Jainus (Monogenea: Dactylogyridae) Parasitizing Gills of Brazilian Freshwater Fishes Supported by Morphological and Molecular Data † - Yamada, Priscilla de Oliveira Fadel [UNESP]; Müller, Maria Isabel; Zago, Aline Cristina [UNESP]; Yamada, Fabio Hideki; Ebert, Mariana Bertholdi [UNESP]; Franceschini, Lidiane [UNESP]; da Silva, Reinaldo José [UNESP] (My University, 2023)
The present study describes three new species of monogeneans parasitizing the gills of anostomid fishes from the Upper Paraná River basin, southeastern Brazil: Jainus beccus n. sp. and Jainus radixelongatus n. sp. on Leporinus friderici, Leporinus octofasciatus, Leporinus striatus, and Megaleporinus elongatus; and Jainus ornatus n. sp. on L. friderici. The new species differ from other congeners by the morphology of the accessory piece. There is a semicircular distal portion resembling a “bird’s beak” in Jainus beccus n. sp. It composed of two subunits—one ventral and more sclerotized, sickle-shaped, and another dorsal with three projections—in Jainus radixelongatus n. sp. There are two elongated and sclerotized subunits, both of which have a sickle-shaped distal portion, in Jainus ornatus n. sp. Supplementary observations not reported in the original descriptions of the type-species Jainus piava Karling, Bellay, Takemoto & Pavanelli, 2011 are proposed, as follows: the presence of a thin and delicate ventral bar, which can vary greatly in shape; an accessory piece not articulated with the MCO’s base. This paper provides the first phylogenetic study based on LSU rDNA and COI mtDNA gene sequences for Jainus, improving and clarifying the understanding of host–parasite relationships in neotropical characiforms.
Keywords: Ancyrocephalinae; COI mtDNA; ectoparasites; Jainus; LSU rDNA; neotropical region; new species; phylogeny; taxonomy